"НАЦІОНАЛЬНИЙ ВИМІР ГЕНОЦИДУ": СУЧАСНА УКРАЇНСЬКА ІСТОРІОГРАФІЯ ГОЛОДОМОРУ 1932-1933 РР. (Zaporizhzhia Historical Review, 2021)
In the artticle the historiography of national aspect of the problem Ukrainian famine of 1932-1933.